Behavioral risk factors for asymptomatic bacteriuria in pregnant women - Campos Solórzano, Teodardo (2014)
Objectives: To determine behavioral risk factors related to asymptomatic bacteriuria in pregnant women. Design: Case control study. Setting: Daniel Alcides Carrion National Hospital, Callao, Peru. Participants: Pregnant women. Interventions: From July 2010 through June 2011 pregnant women with positive urine cultures and without urinary tract infection (cases) and asymptomatic pregnant women with negative urine culture (controls) were studied. Chi square and bivaried logistic  egression were used for association and multivaried logistic regression with age, origin, education level, marital status, occupation, parity and use of bladder catheter. Main outcome measures: Behavioral risk factors for asymptomatic bacteriuria. Results: Association was found between: a) restraining voiding and asymptomatic bacteriuria, ORcrude 3.694 (95% CI: 2.556-5.356);  association remained when adjusting odds ratio (OR) for probable confounding variables, OR: 3.4766 (3.057-7.421); b) daily coitus and asymptomatic bacteriuria, ORcrude 1.883 (1.260-2.842); adjusted ORadjusted 1.729 (1.118-2.675) maintained significantly. No association between asymptomatic bacteriuria and hygiene less than six weeks per week was found. Conclusions: Frequency of asymptomatic bacteriuria was three times higher in pregnant women that retained from voiding, and pregnant women who had coitus daily had 70% more possibility of presenting asymptomatic bacteriuria. It is advisable to consider  these findings in counseling pregnant women.Keywords: Asymptomatic bacteriuria, behavioral risk factors, voluntary voiding retention, sex and intimate hygiene.